Specific functionalization of CTAB stabilized anisotropic gold nanoparticles with polypeptides for folding-mediated self-assembly - Wang, Yusong (2013)
Anisotropic nanoparticles stabilized by cetyltrimethylammonium bromide (CTAB) are notoriously difficult to homogenously functionalize using conventional gold–thiol chemistry. Using surface assisted laser desorption time of flight mass spectroscopy and scanning transmission electron microscopy-energy dispersive X-ray spectroscopy, we demonstrate that silver species adsorbed on the particle surface prevent effective surface functionalization. When covered by a thin gold film, particle functionalization was drastically improved. A thiol-containing polypeptide was immobilized on arrowhead gold nanorods (NRs) and was subsequently able to selectively heteroassociate with a complementary polypeptide resulting in a folding-mediated bridging aggregation of the NRs. Despite using arrowhead NRs with a pronounced difference in surface arrangement on the {111} facets on the arrowheads compared to the {100} facets at the particle sides, the polypeptides were efficiently and homogeneously immobilized on the particles after gold film overgrowth.